Cellular and biochemical antileukemic mechanisms of the meroterpenoid Oncocalyxone A. Issue 3 (1st February 2021) - Sbardelotto, Aline Borba; Barros-Nepomuceno, Francisco Washington Araújo; Soares, Bruno Marques; Cavalcanti, Bruno Coêlho; Ramos de Sousa, Rayran Walter; Costa, Marcília Pinheiro da; Pessoa, Otília Deusdênia Loiola; Pessoa, Cláudia; Ferreira, Paulo Michel Pinheiro
ABSTRACT: Oncocalyxone A, a 1, 4-benzoquinone derived from Cordia oncocalyx, exhibits anti-inflammatory, antimicrobial and antidiabetic properties. The aim of this study was to (1) examine the cytotoxic actions of oncocalyxone A on human normal and tumor cell lines and (2) determine mechanistic actions underlying effects upon leukemia cells using cellular and molecular techniques. Antiproliferative studies on cancer cell lines, peripheral blood mononuclear cells, and human erythrocytes were performed using colorimetric assays. To understand cytotoxicity, assessments were performed with HL-60 leukemia cells (8, 16.5, or 33 µM) after 24 hr incubation using light and fluorescence microscopy, trypan blue, flow cytometry, Comet assay, western blot of caspases and poly-ADP-ribose polymerase (PARP), and effects on topoisomerase I and II. Oncocalyxone A exhibited cytotoxic action upon HL-60 cells and dividing leukocytes, but minimal hemolytic action on erythrocytes. Mechanistic investigations demonstrated reduction of cell viability, loss of membrane integrity, cell shrinking, chromatin condensation, blebbings, externalization of phosphatidylserine, caspase activation, PARP cleavage, mitochondrial depolarization, and DNA damage. Pre-treatment with N-acetylcysteine 4 mM significantly reduced DNA damage and prevented membrane integrity loss. Oncocalyxone A displayed free radical dependent antileukemic activity via apoptotic pathways and induced DNA damage in HL-60 cells. Oncocalyxone A possesses structural chemical simplicity enabling it to be a cost-effective alternative. These properties justify further improvements to enhance activity and selectivity and the development of pharmaceutical formulations. Abbreviations Acridine orange, AO; ANOVA, analysis of variance; BSA, bovine serum albumin; DI, Damage Index; DMSO, dimethylsulfoxide; EC50, effective concentration 50%; EDTA, ethylenediamine tetraacetic acid; EB, ethidium bromide; HCT-116, colon carcinoma line; HL-60, promyelocytic leukemia line; IC50, inhibitory concentration 50%; MTT, 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide; OVCAR-8, ovarian carcinoma line; NAC, N-acetylcysteine, PBMC, peripheral blood mononuclear cells; PBS, phosphate-buffered saline; PI, propidium iodide; PARP, poly-ADP-ribose polymerase; RPMI-1640, Roswell Park Memorial Institute medium; SF-295, glioblastoma line; ROS, reactive oxygen species; 7-AAD, 7-amino-actinomycin D; H2 -DCF-DA, 7′-dichlorodihydrofluorescein diacetate.